KEMAMPUAN LITERASI NUMERASI DITINJAU DARI KONEKSI MATEMATIS SISWA - Wahyu Ningrum, Shinta; Fatimatul Khikmiyah; Enny Suryantari (MUST: Journal of Mathematics Education, Science and Technology, 2024)
Numeracy literacy skills can help someone recognize the uses of mathematics in everyday life. This is closely related to students' mathematical connection abilities. Without good mathematical connection skills, students' numeracy literacy abilities will not be optimal. This research aims to describe numeracy literacy abilities in terms of students' mathematical connections. The subjects in this research were three class XI students at SMA Negeri 1 Gresik, each of whom had high, medium and low levels of mathematical connection ability. The data instruments used are tests and interview guidelines. The results of this research show that students with high mathematical connection abilities can solve numeracy literacy questions correctly, while students with middle and low mathematical connection abilities cannot solve numeracy literacy questions correctly. This is because students do not yet understand the basic concepts of calculating operations for dividing fractions in the form of roots and the concept of trigonometry material itself. Based on the research results, it is recommended that students maximize their mathematical connection abilities by increasing their understanding of concepts. So by having good mathematical connection skills you will be able to support good numeracy literacy skills and also to solve math problems, especially AKM questions.